INTRAORAL LYPHOMA ON THE MENTAL REGION: A Case Report : Lipoma Intraoral Pada Regio Mentalis: Laporan Kasus - Wayan Sutresna Yasa; I Made Hendra Cahyadita Nusantara Putra; Kirana Guspiari (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Lyphoma is a benign tumor of mesenchymal origin composed of mature adipocytes, usually separated by a thin fibrous connective tissue capsule. Lyphomas are rare in the oral maxillofacial region (0.1% to 5%). The clinical presentation of intraoral lyphoma is usually an asymptomatic yellowish mass. Case:  This case report present an intraoral lyphoma occurring in the mental region of a 44-years-old man. The patient came with complaints of fullness in his left chin since the last year. Intraoral examination revealed the presence of smooth sessile nodules, moderate in size with yellowish color. Case Management: Surgical excision under general anesthesia is performed to remove the tumor. Discussion: Lyphoma is the most common mesenchymal tumor, but incidence in the oral cavity is rare. The etiology of intraoral lyphoma still unclear, but the possible pathogenesis mechanisms are the “hypertrophy” and “metaplasia” theory. The diagnosis of intraoral lyphoma usually clinical. Techniques such as intraoral radiography, USG, CT and MRI make the diagnosis of these tumors easier.  Histopathology remains the gold standard in the diagnosis of lyphomas.   Intraoral lyphoma treatment is surgical excision. In this case, the intraoral lyphoma located near to the mental foramen so the mental nerve must be protected during surgery using blunt dissection and careful excision. With this technique no complications seen after the surgery. Conclusion: Intraoral lyphomas are rare, clinicians should be able to recognize this tumor. Through this, adequate surgical excision will be performed and the recurrence rate reduced.